National Defense Policy: considerations for a analytical approach - Editorial, Comité; Eissa, Sergio (International Relations, 2017)
Defense policy has not been one of the priorities of Argentine society since the return of democracy. However, a group of actors have "fought" intensely about what to do with the Armed Forces without having agreed on it. This article proposes not only to investigate the factors that may be influencing the debate, but also to propose a roadmap to overcome those obstacles that inhibiting to define the guidelines for a defense policy for the 21st Century. For this purpose defense is understood as a public policy and briefly presents an analytical model to apprehend the bid around the definition of this issue.